2019
DOI: 10.1080/15459624.2019.1617870
|View full text |Cite
|
Sign up to set email alerts
|

Understanding airborne contaminants produced by different fuel packages during training fires

Abstract: Fire training may expose firefighters and instructors to hazardous airborne chemicals that vary by the training fuel. We conducted area and personal air sampling during three instructional scenarios per day involving the burning of two types (designated as alpha and bravo) of oriented strand board (OSB), pallet and straw, or the use of simulated smoke, over a period of 5 days. Twenty-four firefighters and ten instructors participated. Firefighters participated in each scenario once (separated by about 48 hr) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 14 publications
3
34
0
Order By: Relevance
“…For each PAH sample, total PAHs were calculated by summing the concentrations (OVS-XAD-7 air samples ¼ mg/m 3 ; PTFE filters ¼ mg/filter) of the 15 PAHs. Zero was used for non-detectable concentrations of individual PAHs in this summation (Fent et al 2019). For each exposure trial, we calculated the median of the ambient PAH and benzene air concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each PAH sample, total PAHs were calculated by summing the concentrations (OVS-XAD-7 air samples ¼ mg/m 3 ; PTFE filters ¼ mg/filter) of the 15 PAHs. Zero was used for non-detectable concentrations of individual PAHs in this summation (Fent et al 2019). For each exposure trial, we calculated the median of the ambient PAH and benzene air concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The ambient chamber PAH air concentrations in this study (range in medians: 70,700À285,500 mg/m 3 ) were generally higher than levels reported in our previous residential fire and training fire studies 0.017 0.003 0.008 A To estimate the impact of repeated exposure and laundering on PPE protection factors, we calculated the ratio of median ambient chamber air benzene concentrations (Table 1) to benzene under jackets (rib region) B p-value from multiple linear regression of the log-transformed ratios of benzene under jackets in the chest region to median ambient chamber air benzene concentrations by type of jacket closure, controlling for cleaning cycles/exposure trial C p-value from multiple linear regression of the log-transformed ratios vs. cleaning cycles/exposure trial, controlling for type of jacket closure (maximum 78,200 mg/m 3 ) (Fent et al 2018(Fent et al , 2019. This relative increase in concentration may provide a high-concentration challenge to identify possible leakage paths in the PPE, which is similar to traditional laboratory simulant tests (Horn et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was a wide range of variability, naphthalene was the component mainly responsible for total PAH across the studies. Naphthalene predominated (ranges: 66-68%) the total PAH analytes in a fuel package comparison study [35]. As the molecular structure of PAH may contribute to the FC of skin wipe samples, the mean of PAH concentration was estimated using the number of fused aromatic rings (Table 3).…”
Section: Meta-regression Of Skin Wipe Samplesmentioning
confidence: 99%
“…An Australian study provided some evidence that instructors at a training facility for firefighters were at increased risks of overall cancer, testicular cancer, brain cancer, and cutaneous melanoma compared with the general population [ 15 ]. Different combustible materials used during live fire training can produce varying amounts of different carcinogens, including polycyclic aromatic hydrocarbons and volatile organic compounds [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%